Relationships on Old Smoking, Number of Cigarette Consumption Per Day, Body Mass Index (Bmi), Diabetes, Dyslipidemia, and Hypertension with The Decrease of Erection Function Performance in Men 45-64 Years Old Visiting Hospitals - Aldrich Alexander Afeli Tungga (Indonesian Andrology and Biomedical Journal, 2022)
The decrease in erectile function performance is the inability to sustain an erection long enough during intercourse (NIH Consensus Conference, 1993). The etiology of decrease in erectile function performance is multifactorial; organic factors, and psychogenic factors involved in the ability to get and maintain an erection (Agarwal, 2006). The decrease in erectile function performance in this study was measured using IIEF-5 questionnaire. This study is a cross-sectional observative research that use the results of the questionnaire answers of the respondents. Obtained a population of 161 people who were then screened to 109 people who fit the criteria of this research by using insidential sampling method. The results of this study showed a decrease in erectile function performance of 56.88% of the total respondents. Correlation test results showed a significant association of each variable age, duration of smoking, number of cigarettes per day, diabetes, dyslipidemia, and hypertension with a decrease in erectile function performance. Then for Body Mass Index (BMI) in this study did not show any significant relationship with decreased in erectile function performance. This is because the respondents in this study consist only of normal wight (18.5 to 24.9) and over weight (25 to 29.9). Advice given to avoid decrease in erectile function performance is to reduce cigarette consumption, and improve or treat an unhealthy condition such as BMI above normal, Diabetes, Dyslipidemia and hypertension. This study only retrieve data from the questionnaire so that the data are less and incomplete clear risk factors.